Physical Properties of Gel and Edible Plastic from Whey and Tapioca In Various Ratio and pH Value - Lindriati, Triana; ., Herlina; Nafi, Ahmad (UNEJ e-Proceeding, 2014)
Edible plastic usually made from hydrocolloids and could be produced by solvent casting method whereas gel was made before casting. Potential of whey protein combined with tapioca as edible plastic based component was studied at this research. pH of solvent could affect interaction of whey and tapioca duringÂ  gel preparation. The gelâs characters affected on plasticâs characters . The research objectives were to study effect of whey and tapioca ratio and pH of solvent on physical properties of gel and edible plastics. Randomized Factorial Block Design were used. The two factorsÂ  wereÂ  porpotion of whey protein-starch mixture (0%, 20%, 40%, 60%, 80%, 100%) and pH of solvent ( 4, 7 and 9). Increasing of whey porpotion could increase solubility of gel but decrease gelâs lightness and texture. Increasing of pH could increase gelâs solubility and decrease lightness and texture. There was significant effect (pâ¤0,05) of whey porpotion and pH interaction on gelâs characters. Increasing of whey porpotion could increase tensile strength and decrease elongation and solubility of edible plastics but the increasing of tensile strength was not significant (pâ¥0,05). Increasing of pH could increase elongation and decrease tensile strength and plasticâs solubility. There wasnât significant effect (pâ¥0,05) of whey porpotion and pH interaction on edible plasticâs characters. The result showed that whey addition had decreased plasticâs characters even at 100% whey ratio tensile strength and elongation value were zero, edible plastic could not be produced from 100% whey. Keywords: texture, solubility, elongation, tensile strength, interaction